Maritime Education Strategy through CSR Programs in Coastal Communities - Salfhaoctha Friemay Aliefia Poetry; Jamalullail Jamalullail; Mochamad Bobby Alief; Dinda Amelia Putri; Anwar Senoaji (Greenation Research & Yayasan Global Resarch National, 2026)
This study aims to analyze the implementation strategies of Corporate Social Responsibility (CSR) in supporting maritime education and economic empowerment of coastal communities in Tarumajaya District, Bekasi Regency. The main problems faced by coastal communities include low financial management literacy, limited entrepreneurship skills based on local potential, and minimal utilization of digital marketing. This research adopts a qualitative approach with a descriptive-analytical design. Data were obtained through in-depth interviews, observation of training activities, and documentation of CSR programs, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing with source triangulation to maintain data validity. The results of the study indicate that the effectiveness of CSR programs is determined not only by the substance of the training materials, but also by participatory, dialogic, and hands-on practice-based communication strategies. These communication strategies are able to enhance participants’ understanding in business financial record-keeping, foster entrepreneurial awareness based on the added value of coastal resources, and encourage the initial adaptation to digital marketing through social media. Thus, CSR in this study functions as a planned development communication instrument aimed at behavioral change, rather than merely philanthropic activity. This research contributes to the development of a communication strategy model for empowerment-based CSR that positions communication as a medium for sustainable socio-economic transformation of coastal communities.